2010
DOI: 10.1158/0008-5472.can-10-1548
|View full text |Cite
|
Sign up to set email alerts
|

ASNA-1 Activity Modulates Sensitivity to Cisplatin

Abstract: Cancer can be cured by platinum-based chemotherapy, but resistance is a major cause of treatment failure. Here we present the nematode Caenorhabditis elegans as a model to study interactions between the platinum drug cisplatin and signaling pathways in vivo. Null mutation in a single gene, asna-1, makes worms hypersensitive to cisplatin. The metalloregulated ATPase ASNA-1 promotes insulin secretion and membrane insertion of tail-anchored proteins. Using structural data from ASNA-1 homologues, we identify speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…These results explain previous findings that the cellular abundance of Get3 (~17,300 molecules) is up to 10 times higher than that of other members of the GET pathway, such as Get1 (~2,250 molecules), and matches well with the abundance of other molecular chaperones, including Hsp104 (~32,800 molecules) (Ghaemmaghami et al, 2003). Our finding that Get3 appears to serve a dual purpose in vivo is also in excellent agreement with previous studies conducted in Caenorhabditis elegans , which revealed that deletion of the Get3 homologue TRC40 (ASNA1) causes two distinct phenotypes, a severe growth defect and increased sensitivity to cisplatin (Hemmingsson et al, 2010), an anti-cancer drug known to cause oxidative stress. Intriguingly, while both phenotypes were rescued by expression of wild-type TRC40, a TRC40-variant lacking the conserved, redox-sensitive cysteines rescued the growth defect but not the cisplatin-sensitivity (Hemmingsson et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results explain previous findings that the cellular abundance of Get3 (~17,300 molecules) is up to 10 times higher than that of other members of the GET pathway, such as Get1 (~2,250 molecules), and matches well with the abundance of other molecular chaperones, including Hsp104 (~32,800 molecules) (Ghaemmaghami et al, 2003). Our finding that Get3 appears to serve a dual purpose in vivo is also in excellent agreement with previous studies conducted in Caenorhabditis elegans , which revealed that deletion of the Get3 homologue TRC40 (ASNA1) causes two distinct phenotypes, a severe growth defect and increased sensitivity to cisplatin (Hemmingsson et al, 2010), an anti-cancer drug known to cause oxidative stress. Intriguingly, while both phenotypes were rescued by expression of wild-type TRC40, a TRC40-variant lacking the conserved, redox-sensitive cysteines rescued the growth defect but not the cisplatin-sensitivity (Hemmingsson et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that Get3 appears to serve a dual purpose in vivo is also in excellent agreement with previous studies conducted in Caenorhabditis elegans , which revealed that deletion of the Get3 homologue TRC40 (ASNA1) causes two distinct phenotypes, a severe growth defect and increased sensitivity to cisplatin (Hemmingsson et al, 2010), an anti-cancer drug known to cause oxidative stress. Intriguingly, while both phenotypes were rescued by expression of wild-type TRC40, a TRC40-variant lacking the conserved, redox-sensitive cysteines rescued the growth defect but not the cisplatin-sensitivity (Hemmingsson et al, 2010). These results indicate that TRC40 works as a dual-function protein also in higher eukaryotes.…”
Section: Discussionsupporting
confidence: 92%
“…However, only wild-type TRC40 was able to complement for the observed cisplatin sensitivity. These results strongly suggest that Get3’s redox-regulated chaperone functions plays a crucial role in oxidative stress protection in higher eukaryotes as well (119). These are exciting findings but many questions remain open: How does Get3 recognize its client proteins?…”
Section: Get3 – a Redox-regulated Dual-function Protein In Eukaryotesmentioning
confidence: 86%
“…These findings are consistent with previous reports about a potential dual function in the Get3 homologue TRC40 in Caenorhabditis elegans . Deletion of TRC40 was found to cause severe growth deficits and increased sensitivity towards cisplatin (119), an anticancer drug thought to cause oxidative stress in vivo (120). Importantly, complementation studies using either wild-type TRC40 or a mutant variant lacking two of the four cysteines revealed that both proteins rescued the growth defect of a TRC40 deletion strain.…”
Section: Get3 – a Redox-regulated Dual-function Protein In Eukaryotesmentioning
confidence: 99%
“…Recently, Get3/Asna1 was also shown to function, under oxidative stress conditions, as a molecular chaperone that binds unfolded proteins to prevent their irreversible aggregation (18). In Caenorhabditis elegans, Asna1 function is required for larval growth and resistance to cisplatin, an oxidative stress-inducing anticancer drug (19,20).…”
mentioning
confidence: 99%